PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI F SMAN 7 PADANG - Sofira, Dila (Departemen Matematika, 2023)
Mastering mathematical problem solving is one of the goals of learning mathematics. In reality, this ability is still low. This is known from the initial ability test. The group investigation model, where students discuss and solve problems with peers, is used to overcome this low ability. Randomized Control Group Posttest Only Design was used for the Quasy-Experiment study. Sampling was done by simple random sampling. XIF.2 was the experimental sample while XIF.1 was the control. The study found that the group investigation model was better than the conventional model (P-Value = 0.010 < α = 0.05).Keywords– Mathematical Problem-solving, Group Investigation